PERSONAL HYGIENE POST SIRKUMSISI PADA ORANGTUA ANAK PRASEKOLAH - Kadek Primadewi; Siti Zakiah; Adi Cahya Dewi (Jurnal Bakti untuk Negeri, 2022)
Circumcision in Indonesian is known as circumcision or chopsticks which is the guidance of Islamic law for men and women. This study was conducted to determine the knowledge of parents about personal hygiene post circumcision in preschool children. The method used in this research is descriptive analytic. The results obtained based on 52 parents who filled out the questionnaire showed that as many as 42 people had good educational outcomes (80.8%) and as many as 10 people (19.2%) had poor educational outcomes. The conclusion in this study is that parents of preschool children who do circumcision really need to get education about personal hygiene that arises after circumcision is an action to prevent infection and other things that are not expected.